(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
This article highlights some of the challenges facing history teachers in designing and assessing heritage investigation projects in the Further Education and Training (FET) band and the need for teachers to be proactive in terms of their professional development. It also explores ways in which open distance learning (ODL) can address these challenges by providing guidance, encouragement, practical skills training and resource material, especially to those teachers who cannot take their learners to a museum or heritage site for material or logistical reasons. The article is anchored in a qualitative research methodology and reports on student feedback on the Short Course in School History Enrichment offered by the Department of History at the University of South Africa (Unisa) as well as ongoing inquiry into teacher experience of teaching heritage investigation. It also shares the author’s personal reflections based on informal communication with course candidates and other teachers over a period of more than ten years. The article argues that ODL can play a significant role in history skills development at secondary school level in general and in enhancing the self-confidence and skills of teachers having to teach heritage investigation in particular. It also emphasises the value of informal partnerships between the ODL institution and role players in the heritage field and makes a plea for closer cooperation between academic historians, history teachers, the Department of Basic Education and the heritage sector.